De-Silencing the Voice of the Christian Teacher via the Societal Curriculum: - Gentleman Dogara (African Theological Journal for Church and Society)
This study pursued three purposes: Firstly, to discuss what it means for Christian teachers to have a comprehensive working grasp of their calling to Christ’s ambassadorial services; secondly, to consider how the silence of Christian teachers in the education system and Public Square of Nigeria is reflecting lack of a comprehensive working grasp of their calling to Christ’s ambassadorial services with responsibilities in the education sector; thirdly, to reason-out ways in which the societal curriculum can be deliberately engaged to develop a voice for Christian teachers. The study was done through the documentary research approach component of the historical methodology. The study concludes by noting that Christian teachers have a dual mandate as educationists in Christian-based schools, and also non-Christian schools. It is through this mandate that the voice of Christian teachers in Nigeria can be de-silenced via the societal curriculum, towards solidifying education and transformational development in Nigeria.